EXTRACTION AND ISOLATION OF ALKALOIDS OF SOPHORA ALOPECUROIDES AND THEIR ANTI-TUMOR EFFECTS IN H22 TUMOR-BEARING MICE - Chang, AiHua; Cai, Zhen; Wang, ZhiHong; Sun, ShengKai (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Alkaloids of Sophora alopecuroides have good biological activity, and are widely used in clinical settings, which not only have pharmacological activities of anti-cancer, cancer suppression, as well as the inhibition, and killing of various microorganisms; but also possess extensive pharmacological effects on immune system, nervous system and cardiovascular system. The objective of this paper was to extract and isolate total alkaloids of Sophora alopecuroides (TASA), and to study their anti-tumor effects in H22 tumor-bearing mice. Materials and Methods: TASA were extracted and isolated using thin-layer chromatography, and column chromatography; and the isolated compounds were analyzed using nuclear magnetic resonance. The inhibitory effects of TASA on tumor in H22-bearing mice were determined by MTT assay. Results: Three compounds were isolated from Sophora alopecuroides L., which were matrine, oxymatrine and sophoridine, respectively. Meanwhile, mouse H22 sarcoma model was established and different doses of TASA apparently inhibited solid H22-tumor in mice; it inhibited the thymus, and spleen to some extent; the degree of inhibition was more obvious for the spleen. Conclusion: TASA has an anti-tumor effect in H22 tumor-bearing mice.